1997
DOI: 10.1152/jappl.1997.83.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Restricted postexercise pulmonary diffusion capacity and central blood volume depletion

Abstract: Pulmonary diffusion capacity for carbon monoxide (DLCO), regional electrical impedance (Z0), and the distribution of technetium-99m-labeled erythrocytes together with concentration of plasma atrial natriuretic peptide (ANP) were determined before and after a 6-min "all-out" row in nine oarsmen and in six control subjects. Two and one-half hours after exercise in the upright seated position, DLCO was reduced by 6 (-2 to 21; median and range) %, the thoracic-to-thigh electrical impedance ratio (Z0 thorax/Z0 thig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
59
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 28 publications
7
59
0
Order By: Relevance
“…To evaluate the volume within the thoracic region, including the central vessels and the heart, electrodes are positioned at the right side of the neck and as high as possible in the left mid-axillary line with an approximate 5 cm distance between each pair. With this arrangement of the electrodes, high correlations (r > 0.9) are derived to changes in the thoracic blood volume 10,60,67 and near perfectly matching values are obtained in experimental haemorrhage studies (Fig. 3).…”
Section: Electrical Admittancesupporting
confidence: 69%
See 2 more Smart Citations
“…To evaluate the volume within the thoracic region, including the central vessels and the heart, electrodes are positioned at the right side of the neck and as high as possible in the left mid-axillary line with an approximate 5 cm distance between each pair. With this arrangement of the electrodes, high correlations (r > 0.9) are derived to changes in the thoracic blood volume 10,60,67 and near perfectly matching values are obtained in experimental haemorrhage studies (Fig. 3).…”
Section: Electrical Admittancesupporting
confidence: 69%
“…Activation of the muscle pump is especially important following exercise, when blood accumulates in the distended veins of the legs and where the subject continues to hyperventilate. 60 The CBF is affected by the combined effects of lowering of the arterial carbon dioxide tension and a CO reduced by a low CBV. Because fatigue makes movement unattractive, the athlete feels better by lowering the head by leaning on their knees or when lying down, thus neutralizing the hydostatic difference between the heart and the brain.…”
Section: ) Nh Secher and Jj Van Lieshoutmentioning
confidence: 99%
See 1 more Smart Citation
“…Wells et al (1987) demonstrated that the prior cycle bout induced a reduction in plasma volume that tended to be reversed during the subsequent run, whereas during a run-cycle succession the subsequent cycle bout maintained the reduced plasma volume. Hanel et al (1997) showed that the reduced DLco after exercise was related to decreased pulmonary blood volume and a redistribution of central blood flow, as indicated by the measure of atrial natriuretic factor (ANF). The prior cycling segment may thus decrease DLco because of both reduced plasma volume and higher blood volume in the legs that is then shifted to the chest during the subsequent run (Hue et al 2001a, b, c).…”
Section: Introductionmentioning
confidence: 99%
“…Interstitial pulmonary edema has been documented in endurance athletes performing heavy sea level exercise, using imaging techniques such as chest X-ray, magnetic resonance, computed tomography, and scintigraphy (17,36,56). Previous authors measured noninvasively the postexercise extracellular thoracic fluid volume using thoracic impedance monitoring (16). However, this method does not allow visualizing the seat of the water content in the chest.…”
mentioning
confidence: 99%